2018
DOI: 10.1093/rb/rby005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm and remineralization effects of chitosan hydrogel containing amelogenin-derived peptide on initial caries lesions

Abstract: In this study, we have designed a more clinically powerful anti-caries treatment by applying the amelogenin-derived peptide QP5 to the antibacterial carrier material chitosan in a hydrogel (CS-QP5 hydrogel), and characterized its effects on the inhibition of a cariogenic biofilm and the promotion of the remineralization of the initial caries lesions. The results indicated that the CS-QP5 hydrogel sustainably inhibited the growth of the Streptococcus mutans biofilm, lactic acid production and the metabolic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
0
26
0
2
Order By: Relevance
“…Bearing positive surfaces charges, chitosan possesses antimicrobial properties against oral pathogens and biofilms (Arancibia et al 2013; Costa et al 2014) but exhibits low toxicity toward mammalian cells (Kong et al 2010). Hence, chitosan and its derivatives have been used as wound repair materials in bone/periodontal tissue regeneration (Kmiec et al 2017) and as experimental caries prevention materials (Ren et al 2018; Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Bearing positive surfaces charges, chitosan possesses antimicrobial properties against oral pathogens and biofilms (Arancibia et al 2013; Costa et al 2014) but exhibits low toxicity toward mammalian cells (Kong et al 2010). Hence, chitosan and its derivatives have been used as wound repair materials in bone/periodontal tissue regeneration (Kmiec et al 2017) and as experimental caries prevention materials (Ren et al 2018; Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ClyR combined with CMC is more likely to adhere to teeth than ClyR solution, and this can be ascribed to the adhesive property of CMC [22]. Like chitosan, CMC also can form a film on teeth [22,23,53]. While CMC enhanced the anti‐biofilm effect, the addition of ACP also made a difference, which is in line with numerous studies demonstrating that ACP can be used for inhibition of enamel demineralization [30–32].…”
Section: Discussionmentioning
confidence: 63%
“…The ClyR combined with CMC is more likely to adhere to teeth than ClyR solution, and this can be ascribed to the adhesive property of CMC [22]. Like chitosan, CMC also can form a film on teeth [22,23,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohire and Yadav 25 showed that chitosan-containing polyherbal toothpaste had a satisfactory antibacterial activity and significantly reduced the plaque index. Ren et al 26 demonstrated that chitosan hydrogel containing amelogenin-derived peptide could inhibit an S. mutans biofilm and promote the remineralization of initial enamel caries, even in a biofilm model over a prolonged period of time. Carpio-Perochena et al 27 found that chitosan NPs could be applied as a final irrigant during the root canal treatment with the dual benefit of removing the smear layer and inhibiting bacterial recolonization on the root dentin.…”
Section: Introductionmentioning
confidence: 99%